Interactions between Bacteriophages and Eukaryotic Cells - Ramendra Dirgantara Putra; Diana Lyrawati (Scientifica)
As the name implies, bacteriophage is a bacterium-specific virus. It infects and kills the bacterial host. Bacteriophages have gained attention as alternative antimicrobial entities in the science community in the western world since the alarming rise of antibiotic resistance among microbes. Although generally considered as prokaryote-specific viruses, recent studies indicate that bacteriophages can interact with eukaryotic organisms, including humans. In the current review, these interactions are divided into two categories, i.e., indirect and direct interactions, with the involvement of bacteriophages, bacteria, and eukaryotes. We discuss bacteriophage-related diseases, transcytosis of bacteriophages, bacteriophage interactions with cancer cells, collaboration of bacteriophages and eukaryotes against bacterial infections, and horizontal gene transfer between bacteriophages and eukaryotes. Such interactions are crucial for understanding and developing bacteriophages as the therapeutic agents and pharmaceutical delivery systems. With the advancement and combination of in silico, in vitro, and in vivo approaches and clinical trials, bacteriophages definitely serve as useful repertoire for biologic target-based drug development to manage many complex diseases in the future.